One-Class Detection and Classification of Defects on Concrete Surfaces - Faula, Yannick; Eglin, Veronique; Bres, Stephane (Conference proceedings - IEEE International Conference on Systems, Man, and Cybernetics, 2021)
Today, railway infrastructure is subject to regular inspections carried out by image acquisition. Experts need automatic tools to process these images and extract defects. These defects can be classified in two categories : linear defects, like cracks, and surface defects, like spall, humidity, graffiti... Cracks detection has been presented in a previous work, and is based on Local Binary Patterns (LBP) extraction and our FLASH algorithm [1]. In this paper, we propose a new method, using the same LBP descriptors, already extracted, to detect surface defects using generative adversarial networks (GAN). The detection is followed by a classification with a potentially scalable system. Experiments show that our detector achieves better performance than the state-of-the art in application to defect detection.